Spatial Mapping of Air Quality and Respiratory Health Around the Babelan Coal-Fired Power Plant Using the Air Pollutant Standard Index (ISPU) - Aisyah Dian Rahmawati; Juhadi Juhadi (Universitas Lambung Mangkurat, 2025)
Air pollution from coal-fired power plants (PLTU) poses a critical environmental challenge that directly impacts public health, particularly in densely populated areas such as Babelan District, Bekasi Regency. This study aims to: (1) analyze air quality conditions around the Babelan PLTU using the Air Pollutant Standard Index (ISPU); (2) identify spatial distribution patterns of respiratory diseases; and (3) examine the influence of air quality on residents’ respiratory health within a 1–3 km radius of the power plant. A quantitative approach was employed, combining secondary data from the Environmental Agency and local health centers with primary survey data from 175 households selected through disproportional stratified random sampling. Data were analyzed using ISPU calculation, spatial mapping with Geographic Information Systems (GIS), and multivariate regression across dry and rainy seasons. The findings show that PM2.5 is the dominant pollutant, categorized as “Unhealthy” within a 1 km radius during the dry season. The highest incidence of respiratory symptoms such as cough and runny nose occurred within this radius, with decreasing prevalence at 2–3 km. Regression analysis confirms that PM2.5 significantly affects respiratory symptoms (p < 0.05), with the highest R² value (0.68) at the 1 km radius, while the effect declines notably during the rainy season and at greater distances. These results highlight the substantial health risks of PM2.5 exposure for communities living near coal-fired power plants, underscoring the urgent need for emission control measures and targeted public health interventions.